STUDI KELAYAKAN INSTALASI PENGOLAHAN LUMPUR TINJA KOTA SALATIGA - Nasrullah Nasrullah (Universitas Diponegoro, 2007)
Salatiga’s Faecal Sludge Treatment Installation is used for the treatment of faecal sludge which is collected from the septic tank before it’s discarded to the environment. The purpose is to improve the municipal sanitation health condition. Based on the local health department of Salatiga in 2005, 79% Salatiga’s resident has using septic tank facilities. The Faecal Sludge Treatment was planned for the next 20 years with the capacity of 6 m3/day and supported by stabilization system basin. The feasibility study is conducted to determine weather the Faecal Sludge Treatment Installation is suitable or not. Some aspects such as financial, social, economics and technical aspect are important to be considered. The investment cost to establish this installation is IDR 722.207.600 (tax included). From the investment planning evaluation report, FSTI is not supported financially because the period payback had unreachable to the end of planning session, the internal rate of return hadn’t achieved to the lowest rate of interest and the benefit cost ratio is lower than 1 which is 0,98. However the FSTI still can be operated because the other aspects are still support the FSTI construction plan, which is technical, social, economic and regulation aspects.